Orang Muna di Jazirah Tenggara Pulau Sulaweso dan Pohon Kelor - Hasniah Hasniah; Hartini Hartini; Ruwiyah Ruwiyah; Wa Ode Winesty Sofyani; Wa Ode Sifatu (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2022)
Moringa plant (Moringa Oleifera Lam.) has long been cultivated by the Muna people on Muna Island and used as a portion of vegetable food. The purpose of this article is to reveal the existence of Moringa against Muna people who migrate to the southeast peninsula of Sulawesi Island. The theory for reading data is Foucault's thinking about discourse. The results of the study, Muna people who migrated to mount Jati Kendari City are still cultivating moringa. While the Muna people who migrate to Ulunese Village, East Kolono District no longer cultivate Moringa because nature is less supportive. As a result, traditional knowledge and skills of cultivating and utilizing Moringa disappeared. Moringa plants have been scientifically proven to contain highly nutritious nutrients. One of them is to overcome malnutrition in toddlers, which can increase hemoglobin (Hb) levels in adolescent girls. Currently, Moringa has been consumed by other tribes such as the Tolaki, Bugis, Bajo, Moronene, and Javanese. Ideally, these conditions are an economic opportunity for the people of Muna. But in reality in Gunung Jati Village, Kendari City, Moringa is only for family consumption and does not make them cultivate moringa more widely. Similarly, the Muna people in Ulunese Village do not try to cultivate Moringa to meet the needs of consumers. The government should be able to provide counseling on moringa economic opportunities.